Understanding children’s rights in the context of a hybrid legal regime : a socio-legal analysis of child custody issues in Uzbekistan - Urinboyev, Rustamjon; Ibragimov, Diyorbek (International Journal of Law, Policy and the Family, 2025)
This article examines how the principle of ‘the best interests of the child’, as enshrined in the Convention on the Rights of the Child (CRC), is interpreted, constructed, and applied in court cases involving child custody disputes. These disputes provide a globally relevant example of the CRC’s social dynamics, as they often involve interactions and negotiations among diverse professional groups. Specifically, the article investigates how professional actors involved in child custody cases – judges, legal professionals, social workers, community leaders, and religious figures – construct and apply the concept of children’s rights. It further explores how their reasoning, attitudes, and decisions are influenced by broader socio-cultural, religious, and political contexts. To address these issues, the article employs socio-legal frameworks of legal culture and legal pluralism, focusing on a case study of child custody disputes in Uzbekistan, a hybrid legal regime in Central Asia representing a distinctive blend of Soviet, Western, and Islamic legal traditions.
Keywords: Child custody; Child rights; Legal culture; Sociology of law; Uzbekistan